2008
DOI: 10.1177/1046496408323569
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cognitive and Affective Trust in Teams

Abstract: The present research examines the development of two dimensions of trust, cognitive and affective, in student project teams over the course of a semester. Empirical examination of the evolution of multidimensional trust and its unique antecedents was explored. The results show that early trust emerges as a one-dimensional factor early in the life span of a team; cognitive and affective trust emerge as separate components over time; unique and distinct predictors positively and negatively affect early trust, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
163
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(182 citation statements)
references
References 44 publications
(74 reference statements)
13
163
1
5
Order By: Relevance
“…These results have been supported at both the individual (e.g., (Costa 2003)) and team (e.g., (De Jong and Elfring 2010;Palanski et al 2011)) levels. Moreover, prior performance has been shown to have an influence on trust (Walther 1992;McAllister 1995;Webber 2008), supporting a bi-directional relationship between trust and performance.…”
Section: Trust and Performancementioning
confidence: 99%
See 2 more Smart Citations
“…These results have been supported at both the individual (e.g., (Costa 2003)) and team (e.g., (De Jong and Elfring 2010;Palanski et al 2011)) levels. Moreover, prior performance has been shown to have an influence on trust (Walther 1992;McAllister 1995;Webber 2008), supporting a bi-directional relationship between trust and performance.…”
Section: Trust and Performancementioning
confidence: 99%
“…Affect-based trust captures the emotional ties between the trustor and the trustee. This two-component model of trust has received strong empirical support (e.g., (Webber 2008;Wilson et al 2006)) and has become very influential in the field of trust research. Moreover, a recent review by McEvily and Tortoriello (2011) of the measurement of trust identified that the McAllister (1995) scale is one of the most replicated trust measures, further supporting our use of this conceptualization and measurement.…”
Section: What Is Trust?mentioning
confidence: 99%
See 1 more Smart Citation
“…Reciprocal trust between teams has been demonstrated as a longitudinal process where team trust is continually revised based on up to date trustworthiness perceptions following interaction between the teams (Serva, Fuller, & Mayer, 2005). Further empirical evidence from team research also suggests that trust tends to increase over time (Wilson, Straus, & McEvily, 2006), grows more complex and multidimensional as relationships develop (Webber, 2008), and that early trusting beliefs have a significant impact on beliefs two months later (Crisp & Jarvenpaa, 2013). In general, team level results are in line with the proposition that the mechanism through which trust develops is positive exposure to the other party.…”
Section: Newcomer Trust Developmentmentioning
confidence: 99%
“…On the one hand, the monitoring literature has framed transparency and trust as alternative and incompatible mechanisms of control (De Jong & Dirks, 2012;Luhmann, 1979;Piccoli & Ives, 2003). On the other hand, it is rather hard to imagine a well-performing environment either of total transparency devoid of trust, or of total trust devoid of transparency (Webber, 2008). As with another pair of seeming opposites-collaboration and control (Sundaramurthy & Lewis, 2003: 404, Figure 3)-it would seem that an organization, whether at the peer, team, or organizational level, must promote both transparency and trust (De Jong & Elfring, 2010;Loughry & Tosi, 2008).…”
Section: Investigating the Culture Of Transparency And The Role Of Trustmentioning
confidence: 99%